CULTURAL PRODUCT BRANDING, ANTECEDENTS, AND ITS IMPLICATIONS: A STUDY ON THE CONTEXT OF INDONESIAN BATIK - Whony Rofianto; Marissa Grace Haque; Denok Sunarsi; AGUS PURWANTO; Heri Sapari Heri Sapari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This study examines the driving factors for forming positive customer attitudes towards Batik clothing as a cultural product brand and its implications for intention to use. This study will emphasize the symbolic aspect as a driving factor for attitudes. The symbolic aspects are ethnocentrism, product authenticity, and self-image congruence. The study was conducted with a descriptive research design, cross-sectional with data derived from a sample of adolescents in JABODETABEK. The sample was selected using the convenience sampling technique. Data is collected through online surveys. Data analysis and hypothesis testing were carried out quantitatively using the Structural Equation Model approach. The results of the analysis of this study indicate that ethnocentrism, Product authenticity, and self-image congruence positively impact the formation of young people’s attitudes towards Batik, with product authenticity occupying the most dominant ranks. On the implication side, this research also indicates that a positive attitude towards Batik will increase the desire of the younger generation to continue using Batik in the future.